No effect of seasonal variation in training load on immuno-endocrine responses to acute exhaustive exercise - Ronsen, O.; Holm, K.; Staff, H.; Opstad, P. K.; Pedersen, B. K.; Bahr, R. (Scandinavian Journal of Medicine & Science in Sports, 2001)
This study was designed to examine the relationship between seasonal changes in training and competition load, and changes in leukocyte subsets, stress hormones, and interleukin-6 (IL-6) in response to a standardised bout of endurance exercise. In addition, changes in mood states were monitored. Ten male, international Nordic skiers, age 20-29, maximal oxygen uptake 70-82 ml x kg(-1) x min(-1) performed the same incremental treadmill tests to exhaustion at the same time of day (+/-1 h), during the competitive season (in-season HI test) and the recovery season (off-season LO test). The subject filled out a training and competition log (TC score) for three weeks prior to each test and a 65-item Profile of Mood State (POMS) test on arrival at the laboratory. Venous blood for haematological, hormonal, and IL-6 analysis was drawn before and at 0, 15, 30, 60, 120 and 240 min after the test. TC score was more than twice as high during the competitive season (16.0 +/- 3.9) compared to the off-season period (7.0 +/- 4.4). An ANOVA procedure for repeated measures showed no difference in exercise induced changes in concentrations of neutrocytes, lymphocytes, epinephrine, ACTH or cortisol between the in-season HI and off-season LO tests; however, norepinephrine and the IL-6 concentrations were elevated at the in-season HI test compared to the off-season LO test. There were no significant differences in POMS global mood score or sub-scores between the in-season HI and the off-season LO tests. Thus, in a group of elite Nordic skiers, we conclude that a doubling of the training and competition load during the winter season does not alter the leukocyte and stress hormone responses to an incremental exercise test to exhaustion.